Migrant Women Musicians: From Gendered Differentiations to Multisource Inequalities - Marcoux-Gendron, Caroline; Jafarinejad, Kayvan; Sechehaye, Hélène (Intersections, 2022)
This thematic dossier explores the realities of migrant women musicians through fieldwork conducted in Belgium, Canada, and France. Fostering interdisciplinary dialogue, these articles draw from a range of humanities and social sciences. The three papers explore the micro, meso, and macro levels of migration processes by discussing individual career paths as well as socio-cultural and musical profiles, interactions between music network actors, institutional contexts, and the migration mechanisms and cultural policies underlying these musicians’ trajectories. The dossier reveals the numerous challenges that migrant women musicians face and the discriminations and inequalities they suffer based on gendered dynamics, along with multiple other parameters such as ethnicity, race, and religion.